Publishing in small European countries - Kovač, Miha; Gudinavičius, Arūnas (Knygotyra, 2020)
This special issue of Knygotyra is a result of long-lasting collaboration between researchers of few small language countries. We hope this issue will contribute to better understanding the peculiarities of publishing on such markets.